The Interactive Holography as Metaphor and Innovation in Optical Representation in Design - Barcellos, Ekaterina Emmanuil Inglesis [UNESP]; Junior, Galdenoro Botura [UNESP] (Elsevier, 2015)
The strong technological development in the use of virtual images has allowed science, associated with design, to integrate them to different applications in the physical field, interacting with the real world, proposing metaphors and innovative optical representation of imagery processes, redefining and challenging the logic consciousness. With the evolution of 3 D systems, the images were projected to the outside of the screens, earned dimensions beyond the right plan and a concept of “live”, not previously possible. This trend for innovation has carried parts of the holographic universe for interactive applications, where it becomes necessary to achieve and support technology by design projects and the domain anthropometric systems and processes, adapting and integrating the hologram in real time, scale and actual situation. Interactive digital display systems, with picture effects in 3 D hyper-reality, require new platforms that enable seamless interaction between the physical body and holography. This analysis is the proposal to identify and classify some of holographic applications supported by innovative design, demonstrating that from fiction to science fact, the hologram provides a reality by metaphorical and metaphysical bias, compatible and consistent with the behavior of the new societies with joint-impact media. Holograms, replacing real images meet the expectations and interests in technological innovation in step with scientific developments, using a repertoire of design elements grounded by systemic domains and systemic vision.
Keywords: Design innovation; Fuzzy logic; Holography; Human computer interaction (HCI)